The feasibility of virtual reality therapy for upper extremity mobilization during and after intensive care unit admission - Mirthe de Vries; Lise F.E. Beumeler; Johan van der Meulen; Carina Bethlehem; Rob den Otter; E. Christiaan Boerma (PeerJ)
Introduction Early mobilization reduces long-term muscle weakness after intensive care unit (ICU) admission, but barriers (e.g., anxiety, lack of motivation) may complicate patients’ adherence to exercise. Virtual reality (VR) presents immersive stimuli, which may increase motivation and adherence. This study aimed to examine the feasibility of VR-therapy using a VR-headset during ICU- and subsequent general ward admission. Furthermore, physical parameters before and after training were explored. Materials & Methods Ten adult ICU-patients with a median age of 71 [63–79], 70% of male registered birth sex, mechanically ventilated for ≥48 h, and willing to participate, were included. VR-therapy was offered three times a week for 20 minutes in addition to standard care. To train upper extremity functionality, patients were instructed to complete puzzles with increasing level of difficulty. Feasibility was based on patient satisfaction, session efficiency, and adherence levels during the training. Fatigue was measured after each session using the Borg Rating of Perceived Exertion Scale. Patients’ hand-grip strength and Morton Mobility Index (MMI) were evaluated at the start of VR-therapy and after four weeks of training or at hospital discharge. Results On average, patients followed three VR-therapy sessions of 20 min per week with 13 min of actual training time, over the course of 1 to 3 weeks depending on their length of stay. Session efficiency ranged from 25% to 93%. In total, patients adhered to 60% of the VR-therapy sessions. MMI scores increased significantly from the start (26 [24–44]) to the end of the VR-therapy training period (57 [41–85], p = 0.005), indicating improved balance and mobility. Conclusion VR-therapy for upper extremity rehabilitation in ICU-patients is feasible during stay in the ICU and general ward.